Case report: Successful thromboprophylaxis with enoxaparin in a pregnant woman with internal jugular vein agenesis - Di Micco, Pierpaolo; Orlando, Luana; Cataldo, Donato; Imbalzano, Egidio (Frontiers in Medicine, 2022)
Internal jugular agenesis is a vascular malformation that is often associated with a history of recurrent headache. Due to the resulting abnormalities in intracranial venous drainage, it may be complicated by neurological dysfunction, such as intracranial hypertension, intracranial micro-thromboses, and neurodegenerative diseases such as multiple sclerosis. The simultaneous presence of jugular vein agenesis and thrombosis is possible in cases of acute illness, hormonal treatment, pregnancy, hypomobility, or venous drainage abnormalities (VDA) (e.g., May-Thurner syndrome). In particular, the literature still lacks data on thromboprophylaxis in pregnant women with jugular vein agenesis. Here, we report a positive experience with prophylaxis using enoxaparin during pregnancy in a patient with internal jugular agenesis.